ANALISIS PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN DIFERENSIASI PADA MATA PELAJARAN MATEMATIKA MATERI DIAGRAM GAMBAR KELAS II SEKOLAH DASAR - Afiana, Sinta Dina; Azizah, Mira; Handayaningsih, Susi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2024)
This research aims to describe the application of the Problem Based Learning (PBL) model with a differentiated approach in mathematics lessons, specifically on pictogram material for second-grade elementary school students. PBL is a student-centered learning approach that encourages active problem-solving through investigation and collaboration. Differentiated instruction is oriented towards the needs of students, adjusting the learning process according to individual needs, abilities, and interests. This research uses qualitative descriptive methods. The subjects of this study were all second-grade students. The results indicate a diversity of learning styles among students, namely visual, auditory, and kinesthetic. Implementing PBL with a differentiated approach has proven effective in teaching mathematics, particularly in pictogram material, as it provides students with learning facilities tailored to their needs. The application of PBL with a differentiated approach has a positive impact because it allows students to express their potential according to their interests, thereby creating a more meaningful learning experience.